Strengthening Local Economies through the Implementation of Digital Promotion in Tourism Villages and Its Implications for Marine Tourism - Dewi Pratiwi Azis; Ni Gst Nym Suci Murni; I Ketut Budarma; Hajar Dewantara (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This research examines the development of Botolempangan Karst Palace Tourism Village through digitalization and digital marketing approaches. The study combined analysis of existing tourism village management with digital technology-based development strategies. Through an internship and training program, researchers developed tour packages and digital promotional materials, including flyers and profile videos. The study also adopted the AIDDA model (Attention, Interest, Desire, Decision, Action) to optimize the digital marketing strategy. The results showed that the management of Botolempangan Karst Palace Tourism Village still faces challenges, especially in terms of promotion and utilization of digital technology. The training provided includes creating promotional content, utilizing social media, and developing digital marketing skills. This research produced recommendations to improve the quality of human resources of managers, optimize the use of digital media for promotion, and develop a digital application-based management model. The application of digital promotion in tourism villages has opened up new opportunities in the development of marine tourism in Indonesia. By utilizing various digital platforms, coastal tourism villages can introduce the uniqueness of local culture and underwater natural wealth, which is expected to increase marine tourism visits in Indonesia.